Wildlife, conservation, and conflict in Quebec, 1840-1914 - Ingram, Darcy (Nature, history, society., 2013)
Despite the popular assumption that wildlife conservation is a recent phenomenon, it emerged over a century and a half ago in an era more closely associated with wildlife depletion than preservation. In Wildlife, Conservation, and Conflict in Quebec, Darcy Ingram explores the combination of NGOs, fish and game clubs, and state-administered leases that formed the basis of a unique system of wildlife conservation in North America. However, these early strategies were not as forward-focused as they appear. Ingram traces the emergence of a lease-based regulatory system that blended elite forms of sport and conservation. Applied first to British North America's prized salmon rivers, this system came to encompass the bulk of Quebec's hunting and fishing territories. Inspired by a longstanding belief in progress, improvement, and social order based on European as well as North American models, this system effectively privatized Quebec's fish and game resources, often to the detriment of commercial and subsistence hunters and fishers.